2020
DOI: 10.34172/ijhpm.2020.199
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Preventive Behaviour Strategies and Public Perceptions About COVID-19 in Singapore

Abstract: Background: The unprecedented severity of coronavirus disease 2019 (COVID-19) constitutes a serious public health concern. However, adoption of COVID-19-related preventive behaviours remain relatively unknown. This study investigated predictors of preventive behaviours. Methods: An analytical sample of 897 Singaporean adults who were quota sampled based on age, gender, and ethnicity were recruited through a web-enabled survey. Outcomes were adoption of, or increased frequency of preventive behaviours (avoiding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
4
39
0
1
Order By: Relevance
“…In total, 25 studies including 32 different samples and 20,352 participants from Southeast Asia were incorporated in this meta-analysis [22-46]. Of these, 7 studies (28.1%) were of general populations [25,28,30,34,43,44,46], 10 studies included general HCWs (43.8%) [19,22,24,29,31-33,37,40,45], 5 studies included frontline HCWs (18.8%) [27,37-39,41], and only 3 studies (9.4%) referred to adult students [26,36,47]. Most studies were cross-sectional (96.0%) apart from one that was a longitudinal cohort study (4.0%) (Wong et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 25 studies including 32 different samples and 20,352 participants from Southeast Asia were incorporated in this meta-analysis [22-46]. Of these, 7 studies (28.1%) were of general populations [25,28,30,34,43,44,46], 10 studies included general HCWs (43.8%) [19,22,24,29,31-33,37,40,45], 5 studies included frontline HCWs (18.8%) [27,37-39,41], and only 3 studies (9.4%) referred to adult students [26,36,47]. Most studies were cross-sectional (96.0%) apart from one that was a longitudinal cohort study (4.0%) (Wong et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In Singapore, the overall rates of preventative behaviours (e.g. avoiding public transport, social events and hospitals and reducing frequency/duration of shopping and eating out) were reportedly high [34], while another Singaporean study showed that the use of an official WhatsApp channel, providing information updates to the public, was protective against the development of depression [46]. According to Luo et al [53] the use of precautionary measures to prevent the spread of Covid-19 and the access to up-to-date and accurate information were shown to shield from mental health problems.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The long verbal responses by Alexa could be an advantage to special populations who could not read small fonts on smartphones [37], such as the elderly and those with poor eyesight. More importantly, this could be beneficial to users who choose not to touch easily avoidable surfaces in the current COVID-19 pandemic [38]. However, during our evaluations, Alexa seemed to perform poorly with regards to applicability, credibility, accuracy and comprehensiveness of information on COVID-19, despite it being used in various healthcare settings [4,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A critical challenge is to determine how healthcare agencies should respond to changes in healthcare utilization and possible barriers to access healthcare facilities for the public created by the COVID-19 outbreak. Moreover, the lessons learned from the MERS experience in Korea [ 6 ] and other countries demonstrate the importance of understanding the community response [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. To our knowledge, no other study has evaluated the impact of COVID-19 on the demand of healthcare utilization among the general population.…”
Section: Introductionmentioning
confidence: 99%